2011
DOI: 10.1242/jeb.048223
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the energetic costs of living in saline environments: effects of salinity on basal metabolic rate, body mass and daily energy consumption of a long-distance migratory shorebird

Abstract: SUMMARYMany migratory vertebrates typically move between habitats with varying salinities during the annual cycle. These organisms clearly exhibit a remarkable phenotypic flexibility in their 'osmoregulatory machinery', but the metabolic consequences of salinity acclimatization are still not well understood. We investigated the effects of salinity on basal metabolic rate (BMR), body mass and daily energy consumption of a long-distance migratory shorebird, the dunlin (Calidris alpina), outside the breeding seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 74 publications
1
59
0
Order By: Relevance
“…A fundamental challenge for the cell is a change in the osmolarity of the surrounding medium (Pastor et al, 2009). Osmoregulation is a major physiological challenge for numerous vertebrates that are subject to extensive changes in the salinity of their environment (Gutiérrez et al, 2011). Our data suggest that disintegration of the cell membranes was a result of the osmotic pressure gradient following prolonged dwelling in waters with increased conductivity.…”
Section: Resultsmentioning
confidence: 75%
“…A fundamental challenge for the cell is a change in the osmolarity of the surrounding medium (Pastor et al, 2009). Osmoregulation is a major physiological challenge for numerous vertebrates that are subject to extensive changes in the salinity of their environment (Gutiérrez et al, 2011). Our data suggest that disintegration of the cell membranes was a result of the osmotic pressure gradient following prolonged dwelling in waters with increased conductivity.…”
Section: Resultsmentioning
confidence: 75%
“…Shorebirds inhabiting hypersaline habitats rely on hypo-osmotic prey such as brine shrimp and diptera larvae and adults, whose body water content is about 78–87% of body mass [11]. The water content of fly larvae provided in our experiment was 73.3 ± 0.5% [17]. The food and water were replaced three times a day, and salinity levels of residual and fresh water were measured using a conductivity meter (HI 98402).…”
Section: Methodsmentioning
confidence: 99%
“…In birds, this flexible physiological trait is known to show physiological adaptations to ecological conditions [15,16]. A recent study showed that adult individuals of a shorebird species, the Dunlin ( Calidris alpina ) increased their BMR and daily energy consumption by 17% and 20%, respectively, between freshwater and saltwater [17]. This finding provided strong support that maintaining functional osmoregulatory machinery to excrete excess salt imposes significant energy costs, probably owing to the increased size and metabolic intensity of supraorbital saltglands [17,18], the key organ used by air-breathing animals such as many waterbirds, seabirds and some reptiles to ensure survival in saline environments [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the best-studied group (marine fish, which have large surface areas of highly permeable gills) estimates are below 10% of routine metabolic rate (Evans, 2009), even as low as 0.5%. However, shore birds (dunlin, Calidris alpina) showed increases of 17% in basal metabolic rate when their water supply was changed from freshwater to seawater but much of this cost was probably due to an upregulation of osmoregulatory machinery rather than the costs of salt pumping per se (Gutierrez et al, 2011). An alternative approach is to estimate feasible metabolic rates of salt gland tissue.…”
Section: Costs Of Osmoregulationmentioning
confidence: 99%